2016
DOI: 10.1902/jop.2016.150542
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Responsive Hydrogel With an Anti‐Glycation Agent for Modulating Experimental Periodontitis

Abstract: Chitosan-based, pH-responsive hydrogels loaded with PTB can retard the initiation of and facilitate the recovery from experimental periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…As shown in Figure C, the release of drug was greatly accelerated in the first 2 days at pH 5.5 because of the rapid dissolution of chitosan. The burst release of PTB on the first day was prevented compared to our previous investigation of a chitosan‐based hydrogel . In a neutral environment (pH 7.4), approximately 50% of the drug was still in the nanospheres after 1 week, which suggested that the nanospheres were capable of withholding drug release in a physiologically healthy environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Figure C, the release of drug was greatly accelerated in the first 2 days at pH 5.5 because of the rapid dissolution of chitosan. The burst release of PTB on the first day was prevented compared to our previous investigation of a chitosan‐based hydrogel . In a neutral environment (pH 7.4), approximately 50% of the drug was still in the nanospheres after 1 week, which suggested that the nanospheres were capable of withholding drug release in a physiologically healthy environment.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to develop a pH‐responsive drug delivery system with a more sustainable carrier molecule than hydrogel entirely based on the amphiphilic chitosan polymer . Drugs were encapsulated with PLGA and covered with chitosan in a nanosphere.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations